La acción artística como producción narrativa: subjetividades, performance y experiencia en el Penal Modelo Ancón II - Pastor Rubio, Lorena (2019)
This article seeks to reflect on the experience of a performing arts workshop conducted with a group of young men and women in the Ancón II Model Penitentiary in the city of Lima between 2014 and 2018. The study attempts to review how the narratives arise from the subjectivity and, at the same time, configure it, as well as ponder on how the processes and contexts where these narratives are generated constitute important units of analysis to understand the frameworks that produce them. It is proposed that the performance of these young men and women, understood as a corporal action, in its showing doing is capable of generating reflective spaces of encounter and communication with constitutive and transformative power, but also can problematize these discourses, the actions and the links that they constitute.